Personal and social factors influencing students' attitudes towards peers with special needs - Gon?alves, Teresa (2022)
Within inclusive education, it is crucial to consider how students with special needs are valued as members of school community and may fully and actively take part in school-life. The present study aims: 1) to assess students' attitudes towards peers with special needs; 2) to understand how personal factors (age, gender, school achievement and social competence) and social factors (contacting with persons or family member with SN) predict students' attitudes variation. Participants were 200 Portuguese students from 6th to 12th grade. Instruments were administered during class: (i) CATCH (Rosenbaum, Armstrong & King, 1986), comprising a cognitive and an affective-behavior subscale (ii) Social goals Scale (Wentzel, 1993), comprising a social responsibility and a prosocial subscale. We conducted exploratory factor analysis on CATCH and stepwise regression analysis using attitudes as dependent variable. Affective-behavior attitudes were higher in girls and in students with contact with special needs peers and showed moderate correlations with social competence; Cognitive attitudes were higher in older students and were not related with social competence. Prosocial goals were the best predictor of attitudes towards peers with special needs. Results showed that attitudes towards peers with special needs may be influenced by personal and contextual factors. Confirming other findings girls showed more positive attitudes. Also students who have contact with peers with special needs have more positive attitudes, evidencing the potential impact of inclusive settings. The relation found between attitudes and social motivation (mainly prosocial goals) has implications for educational intervention.